LMX differentiation and perceived organizational politics in performance appraisal: Do personality and age matter? - Amaral, Duarte Maria Rebocho Lopes de (2022)
The goal of this dissertation is to study the relationship between leader-member exchange differentiation (LMX Differentiation) and organizational politics in performance appraisal (OPPA) and the possible moderation of Big Five Personality Traits, age and age gap between respondents and their managers. Conducting a vignette study, data for the study was collected through an online survey and shared through social media, in which respondents (N = 113) from various age groups, education background and professional experience, answered question related to LMX Differentiation, OPPA, Big Five and age. After completing the data analysis, a positive significant relationship between LMX Differentiation and perceptions of OPPA was found. This is while, no moderation effect of Big Five nor age/age gap on this relationship was seen. A negative significant relationship was also seen between Employee/Manager Gender Similarity and perceptions of OPPA.